Adapting to climate change to sustain food security - Ziervogel, G.; Ericksen, Polly J. (Wiley, 2010)
Climate change poses considerable challenges to food security. Adapting food systems both to enhance food security for the poor and vulnerable and to prevent future negative impacts from climate change will require attention to more than just agricultural production. This article surveys the multiple components of food security, particularly those relating to access and utilization, which are threatened by the complex responses of food systems to the impacts of climate change. Food security can only be ensured and enhanced with a suite of interventions across activities, ranging from production to distribution and allocation. Although many studies have demonstrated the importance of policy and institutional interventions for ensuring food security after a shock, the climate change impacts and adaptation community have been slow to pick up on these lessons. This article pulls together lessons from the literature on the type of institutional interventions that could be strengthened to enable adaptation in the food system to buffer against climate change at multiple levels, from the local to the global level.